Genetically encoded fluorescent redox sensors - Lukyanov, Konstantin A.; Belousov, Vsevolod V. (Biochimica et biophysica acta, 2014)
Life is a constant flow of electrons via redox couples. Redox reactions determine many if not all major cellular functions. Until recently, redox processes remained hidden from direct observation in living systems due to the lack of adequate methodology. Over the last years, imaging tools including small molecule probes and genetically encoded sensors appeared, which provided, for the first time, an opportunity to visualize and, in some cases, quantify redox reactions in live cells. Genetically encoded fluorescent redox probes, such as HyPer, rxYFP and roGFPs, have been used in several models, ranging from cultured cells to transgenic animals, and now enough information has been collected to highlight advantages and pitfalls of these probes. In this review, we describe the main types of genetically encoded redox probes, their essential properties, advantages and disadvantages. We also provide an overview of the most important, in our opinion, results obtained using these probes. Finally, we discuss redox-dependent photoconversions of GFP and other prospective directions in redox probe development. Fluorescent protein-based redox probes have important advantages such as high specificity, possibility of transgenesis and fine subcellular targeting. For proper selection of a redox sensor for a particular model, it is important to understand that HyPer and roGFP2-Orp1 are the probes for H2O2, whereas roGFP1/2, rxYFP and roGFP2-Grx1 are the probes for GSH/GSSG redox state. Possible pH changes should be carefully controlled in experiments with HyPer and rxYFP. Genetically encoded redox probes are the only instruments allowing real-time monitoring of reactive oxygen species and thiol redox state in living cells and tissues. We believe that in the near future the palette of FP-based redox probes will be expanded to red and far-red parts of the spectrum and to other important reactive species such as NO, O2 and superoxide. This article is part of a Special Issue entitled Current methods to study reactive oxygen species - pros and cons and biophysics of membrane proteins. Guest Editor: Christine Winterbourn. •We review genetically encoded fluorescent probes for intracellular redox events.•Probes for H2O2, GSH/GSSG and NAD+/NADH are discussed.•GFP redding as a redox-dependent process is highlighted.